Factors associated with mortality and neurodevelopmental impairment at 12 months in asphyxiated newborns: a retrospective cohort study in rural Tanzania from January 2019 to June 2022 - Elisa Manzini; Martina Borellini; Paolo Belardi; Evodia Mlawa; Emmanuel Kadinde; Christina Mwibuka; Francesco Cavallin; Daniele Trevisanuto; Agnese Suppiej (BMC, 2024)
Abstract Background Worldwide about 2.3 million newborns still die in the neonatal period and the majority occurs in low- and middle-income countries (LMICs). Intrapartum-related events account for 24% of neonatal mortality. Of these events, intrapartum birth asphyxia with subsequent neonatal encephalopathy is the main cause of child disabilities in LMICs. Data on neurodevelopmental outcome and early risk factors are still missing in LMICs. This study aimed at investigating the factors associated with mortality, risk of neurodevelopmental impairment and adherence to follow-up among asphyxiated newborns in rural Tanzania. Methods This retrospective observational cohort study investigated mortality, neurodevelopmental risk and adherence to follow-up among asphyxiated newborns who were admitted to Tosamaganga Hospital (Tanzania) from January 2019 to June 2022. Neurodevelopmental impairment was assessed using standardized Hammersmith neurologic examination. Admission criteria were Apgar score < 7 at 5 min of life and birth weight > 1500 g. Babies with clinically visible congenital malformations were excluded. Comparisons between groups were performed using the Mann-Whitney test, the Chi-square test, and the Fisher test. Results Mortality was 19.1% (57/298 newborns) and was associated with outborn (p < 0.0001), age at admission (p = 0.02), lower Apgar score at 5 min (p = 0.003), convulsions (p < 0.0001) and intravenous fluids (IV) (p = 0.003). Most patients (85.6%) were lost to follow-up after a median of 1 visit (IQR 0-2). Low adherence to follow-up was associated with female sex (p = 0.005). The risk of neurodevelopmental impairment at the last visit was associated with longer travel time between household and hospital (p = 0.03), female sex (p = 0.04), convulsions (p = 0.007), respiratory distress (p = 0.01), administration of IV fluids (p = 0.04), prolonged oxygen therapy (p = 0.004), prolonged hospital stay (p = 0.0007) and inappropriate growth during follow-up (p = 0.0002). Conclusions Our findings demonstrated that mortality among asphyxiated newborns in a rural hospital in Tanzania remains high. Additionally, distance from home to hospital and sex of the newborn correlated to higher risks of neurodevelopmental impairment. Educational interventions among the population about the importance of regular health assessment are needed to improve adherence to follow-up and for preventive purposes. Future studies should investigate the role of factors affecting the adherence to follow-up.